Harmony With Enviroment Secret of The Succes Story? - Haikal, Husain (Millah: Journal of Religious Studies, 2016)
This autobiography is a part of history, as many parts of its content reveal dynamic aspects of life in West Sumatera. Its author provides the importance of living in harmony with the environment.